2018
DOI: 10.1002/2017ja024573
|View full text |Cite
|
Sign up to set email alerts
|

MLT Plasmapause Characteristics: Comparison Between THEMIS Observations and Numerical Simulations

Abstract: We perform a statistical comparison of the global behavior of the THEMIS observed and simulated plasmapause in the geomagnetic equatorial plane. Simulation is based on the interchange instability mechanism. Analyzing plasmapause positions (LPPs) from the period July 2008 to December 2012, we derived formation and propagation characteristics of the main plasmapause, which reflect the most probable global plasmapause behavior. The results suggest a global eastward azimuthal plasmapause propagation and a radial p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
28
2

Year Published

2019
2019
2020
2020

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 14 publications
(36 citation statements)
references
References 33 publications
6
28
2
Order By: Relevance
“…The simulation outputs for all investigated cases clearly show that the initial plasmapause radial motion (erosion or expansion) occurs at the nightside, more intense around postmidnight. This is in accordance with the strongest E5D field in these MLT sectors, lower conductivity, but may be influenced with the simulation starts at 02 MLT (as discussed in detail in Verbanac et al, 2018). For different changes in the E-Field (different Kp jumps: e.g., Kp increase and Kp decrease), the formation of the new plasmapause Journal of Geophysical Research: Space Physics 10.1029/2019JA026768 can be noted in slightly different night MLT sectors (this will be noted below when describing main plasmapause with specific structures).…”
Section: Characteristics Of the Plasmapause Simulated With Kp Jumps supporting
confidence: 86%
See 4 more Smart Citations
“…The simulation outputs for all investigated cases clearly show that the initial plasmapause radial motion (erosion or expansion) occurs at the nightside, more intense around postmidnight. This is in accordance with the strongest E5D field in these MLT sectors, lower conductivity, but may be influenced with the simulation starts at 02 MLT (as discussed in detail in Verbanac et al, 2018). For different changes in the E-Field (different Kp jumps: e.g., Kp increase and Kp decrease), the formation of the new plasmapause Journal of Geophysical Research: Space Physics 10.1029/2019JA026768 can be noted in slightly different night MLT sectors (this will be noted below when describing main plasmapause with specific structures).…”
Section: Characteristics Of the Plasmapause Simulated With Kp Jumps supporting
confidence: 86%
“…Thus, the width of T lag values affected by the changes in the correlation reflects the azimuthal extension of the structure. On the other side, the results by Verbanac et al (2018) suggested that the T lag belts reflect the MLT range of the plasmapause formation. Since both results seem to be physically plausible, and not necessarily exclusive, we suggest that this issue has to be further investigated.…”
Section: Discussionmentioning
confidence: 98%
See 3 more Smart Citations